Rapport in same and mixed neurotype groups of autistic and non-autistic adults. - Foster, Sarah J; Ackerman, Robert A; Wilks, Charlotte EH; Dodd, Michelle; Calderon, Rachel; Ropar, Danielle; Fletcher-Watson, Sue; Crompton, Catherine J; Sasson, Noah J (Autism: The International Journal of Research & Practice, 2025)
Although autistic adults may establish better dyadic rapport with autistic relative to non-autistic partners, it is unclear whether this extends to group settings. The current study examined whether rapport differs between autistic groups, non-autistic groups, and mixed groups of autistic and non-autistic adults, and whether differing diagnostically from the rest of the group results in lower rapport. One hundred and forty-three adults were assigned to one of four group types of four participants each: all-autistic, all-non-autistic, non-autistic majority (three non-autistic, one autistic), and autistic majority (three autistic, one non-autistic). Groups participated in a 5-minute building activity and afterwards completed a 5-item rapport measure assessing their experience. The all-autistic groups did not differ on overall rapport from the all-non-autistic groups and had significantly higher rapport on two items (enjoying the interaction and friendliness of the group) than both types of mixed groups. At the individual level, autistic participants expressed more ease and enjoyment when interacting with other autistic adults relative to non-autistic adults, and their rapport declined as more non-autistic participants were included in the group. In contrast, rapport for non-autistic participants remained relatively consistent regardless of group composition. We discuss potential reasons why autistic participants were more affected by group composition than non-autistic participants. Autistic adults sometimes get along better with other autistic people compared to non-autistic people, but so far this has only been studied in two-person interactions. This study examined how well autistic and non-autistic people develop rapport in a group setting and whether rapport differs when group members share or do not share a diagnosis. We assigned 143 adults to 36 groups of four adults each. Some groups only had autistic members, some only had non-autistic members, and some were "mixed" groups of autistic and non-autistic members. Groups participated in a tower-building task for 5 minutes and afterwards completed a survey about rapport with the group. The groups of all-autistic participants expressed that their interactions were more enjoyable and friendly than the mixed groups. Autistic participants reported lower rapport when interacting with non-autistic adults, while non-autistic participants reported similar rapport whether interacting with autistic or non-autistic group members. Overall, findings are not consistent with a social deficit model of autism, as autistic adults often established rapport with partners in a group setting. Their level of rapport, however, depended strongly on the social context, particularly whether other autistic people were also in the group.